Orris and Timble : lost and found - DiCamillo, Kate (DiCamillo, Kate. Orris and Timble (Series), 2025)
"Orris the rat and Timble the owl are unlikely friends. Each night, Timble visits Orris in the barn and listens to his stories. But Timble is growing up, and one evening when the owl doesn't appear as usual Orris wonders if Timble has forgotten him. Is their friendship over? Or could it be that Timble has a tale of his own to share?" --